Nietzsche e a moral como problema: da cosmologia à ética do arco - David Neto, Álvaro Henriques (2019)
This paper intends to examine Nietzsche's critique of morality. Thus, in addition to consigning his well-known diatribe to Platonic-Christian morality, which is too much recorded in his program, it intends to reflect on the scope and leitmotiv of criticism itself. At the core of this dissertation, it means to peer, supported also in a cosmological hypothesis verifiable in its project and here flattened, if other morals arise from bitter writings. In this way, it aims to offer responsive notes to the suspicion of some moral iconoclasm advocated by the philosopher. The search for descriptions capable of engendering – with some vigor – intuitions based on the existence of a positive moral philosophy are also part of the plexus of objectives of this exposition. That is, one tries to verify, from the interweaving of some notions, if there is a “sayyes” oriented to the moral. This leads, necessarily, to the search of evidence that, together, will be able – or not – to reveal the experience of an ethical project inserted in the Nietzsche's philosophy. For this, two movements are essential: one adherent to the attempt to investigate the investigative path (the genealogical method) and its findings; and the other one already mentioned, that shows itself in the identification of a cosmological hypothesis that crosses his writings. In this trajectory, the works of the intermediate and late periods are used with more intensity. This is because, as will be seen, from Human, all too human to Ecce Homo, the reflections on morality occupy privileged space.